2008
DOI: 10.2478/v10051-008-0010-x
|View full text |Cite
|
Sign up to set email alerts
|

How Public Relations Impact on a Company's Effectiveness

Abstract: The role of public relations is dealing with the identification of organization's strategic public and developing communications programs for building solid, open and trusting relations with them. Many companies have taken a limited view of the impact that public relations can have on company's overall effectiveness. This paper consists of two parts: the theoretical framework for the role of public relations in the overall effectiveness of the company and an empirical analysis based on the primary data collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
1
0
Order By: Relevance
“…"How public relations impact on a company's effectiveness". [2] A cross sectional descriptive study was conducted in Mahatma Gandhi medical college and research institute, Pondicherry on 152 in patients, which revealed significant association between age, nature of admission and patient satisfaction. The study findings also revealed that there is a definite co relation between gender and patient satisfaction.…”
Section: Literature Surveymentioning
confidence: 99%
“…"How public relations impact on a company's effectiveness". [2] A cross sectional descriptive study was conducted in Mahatma Gandhi medical college and research institute, Pondicherry on 152 in patients, which revealed significant association between age, nature of admission and patient satisfaction. The study findings also revealed that there is a definite co relation between gender and patient satisfaction.…”
Section: Literature Surveymentioning
confidence: 99%
“…Public relations (PR) is aimed to deal with the organization's image in public opinion and develop communications strategies to build strong relationship with them. Every company can create a public relations program, despite of limited budget or number of staff 12 . Effective public relations help managers to develop and maintain a positive reputation of a companies.…”
Section: Forms Of Promotionmentioning
confidence: 99%